Uterus procurement from deceased donor for transplantation. (10th November 2021) - Castro, Felipe; Ejzenberg, Dani; Pinheiro, Rafael S.; Ducatti, Liliana; Arantes, Rubens M.; Nacif, Lucas; Waisberg, Daniel; Martino, Rodrigo B.; Santos, Vinicius R.; Soares, Jose Maria; Baracat, Edmund Chada; D'Albuquerque, Luiz Augusto Carneiro; et al.
Summary: Women with absolute uterine factor infertility cannot get pregnant. The current experience in uterine transplantation is limited and the use of a deceased donor uterus in this area is incipient after some initial unsuccessful attempts. The birth of healthy babies through this modality in four different centers has given a new impetus to the use of this transplantation technique. We aimed to develop a technique for uterus procurement and preparation for transplantation from a brain dead donor. Fifteen uteri were retrieved from multi‐organ donor patients, 10 of these were used in bench surgeries with the proposed technique. All procedures were performed after obtaining family's consent. This study allowed the clinical use of two of the 15 organs that were procured for transplantation. One of these organs resulted in the first live birth worldwide using a uterus transplanted from a deceased donor, a landmark in reproductive medicine. Another outcome was the optimization of the surgical technique involving less manipulation of the uterine vascular pedicles. The success of this novel technique suggests that the proposed model can be replicated and optimized further to facilitate the transplantation of uterus from deceased donors. Abstract : This manuscript resumes a Brazilian and Colombian experience with fifteen uterus retrieval from deceased donors, it explains the surgical technique evolution and compares it with other experiences around the world in the same field.